2015
DOI: 10.2308/apin-51401
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Need for Transparent Disclosures of Political Campaign Contributions and Lobbying Expenditures by U.S. Private Prison Corporations

Abstract: Transparency is a fundamental principle of good corporate governance. A disclosure is an important mechanism that enhances corporate governance through increased transparency and better informed stakeholders. When a government operation contractually assigns prison services to a nongovernment for-profit entity, then that entity is fulfilling a public interest role of incarceration and should be accountable to the citizen taxpayers (i.e., the stakeholders). Accountability is important. But what happens to accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…IFRS adoption relates to the increasing in disclosure and decreasing in the choice of accounting method (Ashbaugh & Morton, 2001;Scott, 2015). The study results of the of Chen, Tang, Jiang, & Lin (2010) showed that after the obligatory adoption of IFRS in the European countries, the earnings mana gement is declined with evident from a decrease in the discretionary accruals and increasing the accruals quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFRS adoption relates to the increasing in disclosure and decreasing in the choice of accounting method (Ashbaugh & Morton, 2001;Scott, 2015). The study results of the of Chen, Tang, Jiang, & Lin (2010) showed that after the obligatory adoption of IFRS in the European countries, the earnings mana gement is declined with evident from a decrease in the discretionary accruals and increasing the accruals quality.…”
Section: Resultsmentioning
confidence: 99%
“…The adoption of IFRS (gradual strategy) in Indonesia begun in 2012 (Institute of Indonesia Chartered Accountants, 2009). Institute of Indonesia Chartered Accountants (IAI) proclaimed that the adoption of IFRS has proven to enhance the increase of disclosures and the decreasing number of accounting methods' options (Ashbaugh & Morton, 2001;Scott, 2015).…”
mentioning
confidence: 99%
“…To avoid potential litigation, private prisons are very protective of information concerning how they are performing. Extending public records laws to private prisons can be an effective means of ensuring transparency and accountability (Scott, 2015;Tartaglia, 2014). Private prisons perform a core governmental function relating to imprisonment.…”
Section: Which Sector Provides Higher Quality Of Confinement?mentioning
confidence: 99%
“…There have been concerns that private prison corporations lobby for legislative changes involving increased use of private confinement (Lippke, 1997;Scott, 2015). Private prison corporations have donated millions of dollars to politicians who would pass legislation promoting harsher sentences, such as "three-strikes," mandatory minimum sentencing, truth in sentencing, and anti-immigration laws (Justice Policy Institute, 2011).…”
Section: Whether Prison Privatization Leads To System-wide Improvement or Deterioration In Prison Performance?mentioning
confidence: 99%
“…Participating in eugenics (Graham et al 2018) and normalizing violence regarding Indigenous populations (Neu, 2000 andNeu &Graham, 2006) reveal symbolic and physical violence as well. Studying incarceration, researchers describe the dynamics of power, profits and violence (Andrew, 2007(Andrew, , 2011Lehman et al 2018;Mennicken, 2013;Scott, 2015;Taylor and Cooper, 2008). As such, "Accounting becomes an eminently suitable technology to manage and enact violence on racialized populations because of its capacity to de-humanize them or render them invisible as people" (Annisette & Prasad, 2017, p. 9).…”
mentioning
confidence: 99%